Regulatory approximation under ALECA: Assessing the economic and social effects on the Tunisian agricultural sector - Werner G. Raza; Bernhard Tröster; Rudi von Arnim; Jihen Chandoul; Chafik Ben Rouine (Austrian Foundation for Development Research (ÖFSE), 2022)
The negotiations on a deep and comprehensive free trade area (DCFTA) between Tunisia and the European Union (EU) have been ongoing since 2015. Better known by its French acronym - Projet d'accord de libre-échange complet et approfondi' (ALECA) - the agreement aims for an ambitious liberalisation of trade and investment in order to integrate Tunisia's economy further into the EU single market. In this study, the authors explicitly consider the costs that Tunisian producers have to incur in the process of regulatory approximation of agricultural standards to EU regulations through ALECA. Based on estimations of compliance costs from interviews with Tunisian exporters to the EU, the effects of regulatory adjustment to EU regulations and private standards in agricultural and food sectors are simulated in the ÖFSE Global Trade model. Moreover, the effects of bilateral reductions in tariffs and quotas and potential changes in productivity and NTM trade costs are taken up in interrelated scenarios. With this approach, the authors are able to provide a more comprehensive picture than previous studies of the multiple implications of ALECA for the agricultural sector in Tunisia. Our assessment concludes that ALECA has significant downside risks, as value-added in Tunisian agriculture might decline by up to 8.3 %. These effects need to be considered in the negotiations and in the broader context for sustainable agricultural development in Tunisia.
Keywords: 330; Agraraußenhandel; Freihandelsabkommen; EU-Binnenmarkt; EU-Lebensmittelrecht; Anpassung; Landwirtschaft; Befolgungskosten; Schätzung; Tunesien